Narrativas seriadas complexas: a construção da personagem na série boneca russa - Leite, Nayara Klécia Oliveira (2022)
This research aims to analyze the construction of the character Nadia Vulvokov, protagonist of the Netflix series Russian Doll. Narratology served as an analytical basis for understanding not only the character category, but also narrative time and focus, due to the relevance in the narrative context of the series, as well as the relationship that these categories establish with each other throughout the series. It also analyzes the unconventional way in which the categories time and focus are constructed in the series from the concept of complex narratives, which made it possible to observe complexifying aspects that intertwine and contribute to the construction of the character in the manipulation of time in a loop, as well as as in the change of narrative focus from the arrival of a new character who starts to co-star in the series. In the field of character, we seek to understand how the fictional serial narrative has built views on the feminine and increasingly represented “difficult women”, or complex women, capable of breaking with stereotyped construction patterns, presenting characteristics closer to the antithesis. -heroism for its imperfections and ambiguities than for the impeccability of the heroines of yore. The dialogues and intertextualities that the series develops, mainly from the Russian or matrioska dolls and mirrors, made it possible to deepen Nadia's analysis and revealed essential subjectivities for the understanding of the character's journey. The Russian Boneca series presents, therefore, a complex narrative, both in terms of the manipulation of narrative time and the focus, but, especially, by the construction of characters that differ from conventional patterns of representations, especially female, pointing to a post-modern trend. - modernity of these productions in the context of serial fictional narrative.